PENDELEGASIAN KEWENANGAN DALAM PENGELOLAAN HUTAN: Studi Kasus Kelompok Tani Hutan (KTH) Kemasyarakatan Sedyo Makmur Kecamatan Semanu, Kabupaten Gunungkidul, Daerah Istimewa Yogyakarta - Rijal Ramdani (Publisia: Jurnal Ilmu Administrasi Publik, 2016)
The aim of this research is to evaluate the engagement of local community in protecting forest areas as delegation mechanism given by government. According to some scholars, government’s authority could be trasnfered to community. However, in the fact that there are only a few cases can be run succeeded. Nevertheless, the final analysis of this research shows the successful of the implementation. There are three main factors as the result; firstly, based on regulation of HKm, its contain is very open for community to involve in the program; secondly, there is a huge opprtunity for NGO’s to empower the capacity building of local community; thirdly, there is a political interest from local government to encourage local community involvement. Consequently, the community has an enough confidence and an ability to run the implementation of HKm. The data of the research was conducted by doing deep interview with several key informants and also occurring Focus Group Discussion with other important stakeholders. DOI: https://doi.org/10.26905/pjiap.v1i2.440